2004
DOI: 10.1099/ijs.0.02928-0
|View full text |Cite
|
Sign up to set email alerts
|

Repeat-type distribution in trnL intron does not correspond with species phylogeny: comparison of the genetic markers 16S rRNA and trnL intron in heterocystous cyanobacteria

Abstract: Leu UAA (trnL) intron sequences are used as genetic markers for differentiating cyanobacteria and for constructing phylogenies, since the introns are thought to be more variable among close relatives than is the 16S rRNA gene, the conventional phylogenetic marker. The evolution of trnL intron sequences and their utility as a phylogenetic marker were analysed among heterocystous cyanobacteria with maximum-parsimony, maximum-likelihood and Bayesian inference by comparing their evolutionary information to that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…In these examples, however, we are unable to distinguish inter-locus recombination between trnL and the other loci from intra-locus recombination within trnL between the P6b stem-loop and the rest of the intron. It has been shown that these two stem-loop types have a punctate distribution on phylogenies inferred from the remainder of the trnL locus (Oksanen et al, 2004). The two stem-loop types are also spread across our trnL phylogeny (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…In these examples, however, we are unable to distinguish inter-locus recombination between trnL and the other loci from intra-locus recombination within trnL between the P6b stem-loop and the rest of the intron. It has been shown that these two stem-loop types have a punctate distribution on phylogenies inferred from the remainder of the trnL locus (Oksanen et al, 2004). The two stem-loop types are also spread across our trnL phylogeny (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…The data on Pseudocyphellaria cyanobionts from New Zealand (Summerfield et al 2002, Rikkinen 2004) pose interesting, but uncertain interpretations. Although Rikkinen (2004) in his tRNA analysis avoided the P6b stem loop shown to be unsuitable for phylogenetic analysis (Oksanen et al 2004), tRNA data are less precise than 16S rRNA data. Still, the data indicate that Pseudocyphellaria may have a wider cyanobiont selectivity than realized today.…”
Section: Discussionmentioning
confidence: 99%
“…2002, Rikkinen 2004) pose interesting, but uncertain interpretations. Although Rikkinen (2004) in his tRNA analysis avoided the P6b stem loop shown to be unsuitable for phylogenetic analysis (Oksanen et al. 2004), tRNA data are less precise than 16S rRNA data.…”
mentioning
confidence: 99%
“…The most commonly used gene locus in the earlier studies has been the group I intron in the tRNA Leu gene. This locus has been used to distinguish different strains of both symbiotic and free‐living Nostoc (e.g., Paulsrud and Lindblad, 1998; Paulsrud et al., 1998, 2000; Costa et al., 1999, 2001; Oksanen et al., 2002; Summerfield et al., 2002; Linke et al., 2003; Oksanen et al., 2003; Wirtz et al., 2003). Some other loci have also been utilized for cyanobacterial studies.…”
mentioning
confidence: 99%